Instability studies of an 'O'-ring flexibly supported, gas bearing, mounted, cool air unit. - McLuckie, I. R. W. (Cranfield University, 1990)
A Cool Air unit (C. A. U. ) is powered by air bled from the engine and supplies cool air to the avionics and cockpit of the aircraft. Essentially a small turbo machine, the rotor is mounted upon two plain (gas) air bearings, which are flexibly supported by elastomeric '0'-Rings. The project objectives were to investigate, experimentally and theoretically, the mechanism of dynamic instability, half frequency whirl (HFW) observed in the C. A. U design, and hence evaluate methods by which it can be best controlled. Two main areas of study were embarked upon. Firstly a steady state aerodynamic study, based on an existing single bearing rig, to evaluate the extent of aerodynamic operation and single bearing instability (HFW). This Test Rig did not have '0'-Ring flexibility. Bearing L/D tested were 2,1.5 and 1.0, with variable loading of 18-1 -º 51.2N and speeds of 6000 -º 40000 Rpm in approximately 5000 Rpm intervals. the theoretical study investigated non-linear effects of air film pressure distribution. Secondly a Dynamic instability study of HFW was carried out on a newly designed Test Rig, simulating small turbo machines and the C. A. U.. Three bearing types were evaluated, Aerodynamic, Hybrid and Hybrid porous. With L/D of 1.0. '0'-Ring Centres varied from 0.17 4 0-83 of bearing length. Viton and Silicon materials were tested with 70 shore hardness. Rotor mass, inertia, asymmetry and unbalance were investigated along with '0'- Ring stiffness and damping variation from air pressure (0 4 120psi). Theory was developed to determine whirl onsets and effects of unbalance, and damping of the support. Non-linear (stagnant areas) of air film detected experimentally, are not explained by Raimondi's theory. Experiments show that Raimondi's theory seriously over estimates the applicable area of fully developed aerodynamic operation. Pressure Profile at onset of Instability tends to a Sommerfeld condition. Temperature was a good indication of lubrication regime. Linear temperature rise curve denotes Aerodynamic operation, and transition to non-linear curve represents onset of Instability (HFW). Authors theory considers non-linearity of air film and suggests a new method of evaluation to improve convergence. Dynamic study of dual bearing rig concludes, first instability onset speed (RSW) can be passed through due to residual unbalance and damping in the '0'-Ring support. Theory developed shows relationship of RSW and HFW effects due to unbalance and damping and results agree well. Viton offered better damping than Silicon. RSW not present in Viton at'0'-Ring centres above 10 mm. HFW not present with Viton below 55,000 rpm. RSW observed with ui /cu = 1.0 and HFW occurred with m /m = 0-493 4 0.58. hybrid porous bearings had lower performance than hybrid, but better than aerodynamic. Hybrid bearings mounted in Viton '0'-Rings offer best performance long term. Aerodynamic bearings can be concluded to be inherently unstable and have limited aerodynamic operation, so should see little use in high speed turbo machinery, including C. A. U. or aircraft applications where zero g loading likely.